The Impacts of Brand Credibility, Brand Prestige, and Online Costumer Reviews on Purchasing Interest - Lusian, Nina Mardati; Harjanti, Sri (AIBPM Publisher, 2023)
This research aims to verify and analyze the impacts of brand credibility, brand prestige, and online customer reviews on purchasing interest of students at the Pembangunan Nasional